Review Of "Facing" At The Beginning Of Notary Action For The General Meeting Of Shareholders (Gms) Electronicly - Habib Adjie (Jurnal Mantik, 2021)
Article 77 of the Limited Liability Company Law (UUPT) states that the General Meeting of Shareholders (GMS) can be carried out under the hands or circularly or conducted in front of a Notary conducted electronically. In this regard, it will try to provide a new interpretation regarding facing the Notary Public not directly but through other media or other media (devices) that help electronically. Traditionally, facing the Notary Public is done and interpreted physically (face to face), namely "The Viewer sees the Notary and the Witness, then the Notary and the Witness see the Facilitator without other media". The meaning of facing like that has been done hundreds of years until now, with the existence of Article 77 of the Company Law, it is connected with Article 90 of the Company Law, namely if the GMS can be held before a Notary Public or before a Notary electronically. The substance of the article has changed the meaning of facing a notary public in the traditional (physical) sense. Henceforth, in the era of information technology, the meaning of facing must be adjusted to the current situation, which can be done electronically.